Plasma surface hardening of medium carbon and tool steel specimens - Ow, Chiew Ming. (2008)
This dissertation presents the works performed on the studies of using plasma arc for surface hardening of ASSAB 760 (medium carbon steel) and ASSAB XW10 (cold work tool steel), with two types of thickness (10mm and 20mm) for both materials.